Physiological performance tests in track and field athletes aged 15 to 18 years - Gurol, B.; Kale, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Physiological performance tests offer some insight into the factors contributing to success and to describe how physiological and technical performance evolves in young track and field athletes. The purpose of this study was to determine the differences in physiological performance test results related to ages in young track and field athletes. Methods Nineteen young female athletes (15-16 age group; height: 165.03±5.73cm, body weight: 55.85±9.04kg, 17-18 age group; height: 163.65±5.71cm, body weight: 54.18±5.98kg ),and twenty-two young male athletes (15-16 age group; height: 172.95±8.18cm, body weight: 56.73±8.97kg, 17-18 age group; height: 176.15±5.15cm, body weight: 59.47±4.89kg) were volunteered to participate the study. Sit and reach test, squat jump, counter movement jump, standing long jump, medicine ball throw, 20m shuttle run test, 10m, 20m, 30m, and 40m sprint tests were performed. Unpaired sample t test was used to analyze the differences in two age groups (15-16 year and 17-18 year) both female young athletes and male young athletes. Results There were statistical significant differences in sit and reach test, squat jump, counter-movement jump, horizontal jump, and medicine ball throw in two young female athlete groups (p<.05). There was a statistical significant difference in medicine ball throw between two young male athlete groups (p<.05). Discussion In conclusion, there were more significant differences between 15-16 ages and 17-18 ages in young female athletes than young male athletes.